Answers

2016-07-01T21:41:59+08:00
2016-07-01T22:01:55+08:00
(4x-7)(x-1)=0 Simplifying (4x + -7)(x + -1) = 0 Reorder the terms: (-7 + 4x)(x + -1) = 0 Reorder the terms: (-7 + 4x)(-1 + x) = 0 Multiply (-7 + 4x) * (-1 + x) (-7(-1 + x) + 4x * (-1 + x)) = 0 ((-1 * -7 + x * -7) + 4x * (-1 + x)) = 0 ((7 + -7x) + 4x * (-1 + x)) = 0 (7 + -7x + (-1 * 4x + x * 4x)) = 0 (7 + -7x + (-4x + 4x2)) = 0 Combine like terms: -7x + -4x = -11x (7 + -11x + 4x2) = 0 Solving 7 + -11x + 4x2 = 0 Solving for variable 'x'. Factor a trinomial. (1 + -1x)(7 + -4x) = 0 Subproblem 1 Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1 Subproblem 2 Set the factor '(7 + -4x)' equal to zero and attempt to solve: Simplifying 7 + -4x = 0 Solving 7 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -4x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -4x = 0 + -7 -4x = 0 + -7 Combine like terms: 0 + -7 = -7 -4x = -7 Divide each side by '-4'. x = 1.75 Simplifying x = 1.75 Solution x = {1, 1.75}
0